(3GdeNJGQ ef eOjM GdeNJGQs - (3jMji Hf jhSa Hf jMji GdCfUGQj, GdUQUQj, LeGd GdOjf CHh RcQjG,J (B656 (3g` s
(3ChdgG (B:s
(3bGd GdTjN LeGd GdOjf jeOM SjOfG eMeO (B((3U(B) (3Ydi bGajI GdgeRI(B: (3SHMGf ef ddhQi ai CQVg OQG hCMSf GdUfGY HGdEJbGf EP HQG s
(3BNQgG (B:s
(3hdG RGdJ dc GdCfhGQ oJgOi hai GdoCNQi dc GdRdai oJgjG Ke GdeNJGQ ef eOM QShd Gddg (B((3U(B) (3ddEeGe LeGd GdOjf hMSHfG Gddg s
(3LGA aj ChdgG Cf GdefJbi aj eOGFM GdQShds
(3hgj eQJHI Ydi GdbhGajs
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B236 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B523s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs